Lithosphere an interdisciplinary approach - q 1961-; ebrary, Inc. (Cambridge ; New York : Cambridge University Press, 2011)
"Presenting a coherent synthesis of lithosphere studies, this book covers a range of geophysical methods (seismic reflection, refraction, and receiver function methods; elastic and anelastic seismic tomography; electromagnetic and magnetotelluric methods; thermal, gravity and rheological models), complemented by petrologic and laboratory data on rock properties. It also provides a critical discussion of the uncertainties, assumptions, and resolution issues that are inherent in the different methods and models of the lithosphere. Multidisciplinary in scope, global in geographical extent, and covering a wide variety of tectonics settings across 3.5 billion years of Earth history, this book presents a comprehensive overview of lithospheric structure and evolution. It is a core reference for researchers and advanced students in geophysics, geodynamics, tectonics, petrology, and geochemistry, and for petroleum and mining industry professionals"--
Machine generated contents note: Foreword; Preface; 1. What is the lithosphere?; 2. Age of the lithosphere; 3. Seismic structure of the lithosphere; 4. Thermal regime of the lithosphere from heat flow data; 5. Thermal state of the lithosphere from non-thermal data; 6. CBL and lithospheric density from petrologic and geophysical data; 7. Electrical structure of the lithosphere; 8. Flexure and rheology; 9. Evolution of the lithosphere; 10. Summary of lithospheric properties; References; Index.
Includes bibliographical references and indexes.
Electronic reproduction.
Keywords: Lithosphere; Geodynamics; Earth -- Crust; Electronic books